An experimental approach to farmer valuation of African rice genetic resources - Tyack, N.; Arouna, A.; Aboudou, R.; Ndjiondjop, M.N. (2024)
Genebanks serve as both providers of valuable traits for breeding programs and repositories of diverse crop genetic material representing society's agricultural heritage. In this study, we use a Becker-DeGroot-Marschak mechanism to elicit the willingness-to-pay of rice farmers in Côte d'Ivoire for small amounts of African rice (Oryza glaberrima) landraces held by the genebank of the Rice Biodiversity Center for Africa, and for seed of newly developed ARICA rice varieties bred using genebank materials. Using a field experiment, we additionally investigate how randomized exposure to and experimentation with small amounts of African rice landrace seed or seed of advanced rice varieties developed by AfricaRice affect how smallholder rice farmers value these novel genetic resources. Surprisingly, we find that farmers generally value having access to African rice landraces at approximately the same level as for advanced rice varieties (and far above market rates for improved seed), and that those farmers who grew landrace seed in the offseason were willing to pay more than those who did not. Our results demonstrate the additional value provided by the conservation of African rice landrace varieties (apart from their use in breeding) and highlight the importance of experimentation in the adoption process.